Journal of Service Science Research - Baek, Seung Ik.; SpringerLink (Online service) (Seoul : The Society of Service Science : Imprint: The Society of Service Science, co-published with Springer.)
Journal of Service Science Research (JoSS) is an international and multidisciplinary journal aiming to serve the needs of researchers and policy-makers as well as practitioners and executives involved in services throughout the world. The journal publishes original, high-quality papers such as theoretical or empirical research, case studies, and review papers. Authors are encouraged to submit papers dealing with any service.
Keywords: Business; Management science; Management; Software engineering; Engineering economics; Engineering economy; Industrial organization; Business and Management, general; Management; Industrial Organization; Software Engineering/Programming and Operating Systems; Engineering Economics, Organization, Logistics, Marketing